The mitochondrial genome of Milvus migrans (Aves, Accipitriformes, Accipitridae), an endangered species from South Korea. Issue 2 (3rd July 2018) - Jeon, Hey Sook; Myeong, Hyeona; Kang, Seung-Gu; Kim, Jung A; Lee, Sang-Hwa; Lee, Mu-Yeong; An, Junghwa
Abstract: The complete mitochondrial genome sequence of black kite, Milvus migrans, one of the most common diurnal raptor, was characterized using next generation sequencing. The whole genome size was 18, 016 bp and consisted of 13 protein-coding genes, 22 tRNAs, 2 rRNAs, a putative control region (CR), and a second control region (pseudo-CR). A frameshift mutation was found in the ND3 gene. Phylogenetic analysis illustrated monophyly of the subfamily Melieraxinae with high statistical support. The genetic resource obtained here will help to resolve taxonomic issues related to subspecies of M. migrans and will act as a starting point for conservation genetics.